LEXICONS IN SATRIA PRAWERTI DANCE - Suryani, Ni Luh Putu (Universitas Suryakancana, 2023)
Satria Prawerti dance contains lexicons and their cultural meanings, but its dancers rarely know and use them, so it can cause language death. This study was designed in the form of a descriptive qualitative method and aimed to find the movements of Â lexicons and their cultural meaning. The obtained data in this study were collected from observation and interviews technique. The result of the study shows that there are 24 lexicons in the movements. Those lexicons are divided into five parts, namely; in the neck movements there are nyeledet kanan, nyeledet kiri, kipek kanan, kipek kiri, ngangget kanan, and ngangget kiri. In the hand movements there are luk nagastru, nangkis kanan, nangkis kiri, and nyerang. In the finger movements there are jeriring. In the body movements there are ngelo kanan, ngelo kiri, ngotag pala, sleag-sleog, agem kanan, and agem kiri. In the leg movements there are tayong, nyeriksik kanan, nyeriksik kiri, tanjek kanan, tanjek kiri, piles kanan, and piles kiri. Some lexicons have different cultural meaning, while the other have the same cultural meaning. In the part of neck movements such as nyeledet kanan, nyeledet kiri, kipek kanan, kipek kiri, ngangget kanan, and ngangget kiri have the same cultural meaning. The other part have same cultural meaning is leg movements, such as; tayong, tanjek kanan and tanjek kiri. The results of this study help preserve regional languages and avoid language death and can be used by dance teachers to make it easier to teach people who want to learn the dance.